PWE-214 The management of incidentally diagnosed pancreatic neuroendocrine lesions: a new tool to evaluate risk of malignancy. (22nd June 2015) - Mills, L; Ramage, J; Prachalias, A; Srinivasan, P; Menon, K; Quaglia, A; Heaton, N; Sarker, D; Ross, P; Basuroy, R; Srirajaskanthan, R
Abstract : Introduction: The regular use of CT scanning has increased the number of incidentally diagnosed, small, asymptomatic pancreatic neuroendocrine tumours (PNETs). Given their uncertain natural history, they pose a management dilemma. Whilst resection offers curative outcomes, the risks of surgery such as with a Whipple–s procedure have led many to adopt surveillance strategies. Patient selection criteria for surveillance lack definitive evidence. Diameter <2cm is often used, but recent work suggests this may not be effective. In order to safely select patients for surveillance, a clearer understanding of the predictors of malignancy is needed. Method: The notes of 233 patients with PNETs of all stages were reviewed for pathology reports. Tumours were defined as malignant if displaying local invasion, nodal involvement or distant metastasis (metachronous or synchronous). Predictors of malignancy were considered using logistic regression. Results: Malignant characteristics were shown to correlate with tumour diameter (r 2 >0.8). However, of 68 tumours <2cm, 21 (31%) developed local or vascular invasion, 18 (28%) nodal metastasis and 16 (24%) distant metastasis. 164 tumours displayed malignant characteristics, 64 had no evidence of malignancy and data was unavailable for 5. Significant univariate predictors of malignancy included diameter (mean 21mm vs. 47mm, p < 0.001), symptomatic presentation vs. asymptomatic (p < 0.001), familial syndromes (p < 0.022) and elevated serum CgA (p < 0.001). Multivariate analysis showed that diameter, symptomatic presentation and elevated CgA were independent predictors of malignancy (p < 0.001, p = 0.001, p = 0.019). The odds ratios were used to construct a model predicting malignancy, shown in Figure 1 . Conclusion: PNETs <2cm often display malignant characteristics. A model incorporating diameter, CgA and symptoms can be used to predict malignancy, and this probability compared to the known risks of surgery in order to help patients and clinicians choose between surgery and surveillance. Disclosure of interest: None Declared. Reference: Cherenfant, J. et al . Predicting aggressive behavior in nonfunctioning pancreatic neuroendocrine tumors. Surgery 2013;154 :785–91; discussion 791–793